2021
DOI: 10.3390/ijerph182111186
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Vibration Foam Rolling with Light and Moderate Pressure on Blood Pressure and Senior Fitness Test in Older Women

Abstract: Vibration foam rolling (VR) can improve flexibility and sports performance. However, blood pressure (BP), heart rate (HR) and senior fitness test (SFT) responses induced by an acute VR session in older women are currently unknown. Fifteen healthy women (72.90 ± 4.32 years) completed three separated randomly sequenced experimental visits. During each visit, they started with a warm-up protocol (general warm up (GW): walking + static stretching (SS), SS + VR with light pressure (VRL), or SS + VR with moderate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…They showed that VFR was more effective than FR in improving pain and hip extension ROM. In addition, VFR for older women has been reported to be effective in improving senior fitness performance when incorporated as a warm-up [ 9 ] as well as an increase in shoulder flexibility when combined with static stretching [ 10 ]. On the other hand, FR and VFR intervention for the ankle plantar flexors was reported to be effective in increasing ROM on the nonintervention side to the same extent [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that VFR was more effective than FR in improving pain and hip extension ROM. In addition, VFR for older women has been reported to be effective in improving senior fitness performance when incorporated as a warm-up [ 9 ] as well as an increase in shoulder flexibility when combined with static stretching [ 10 ]. On the other hand, FR and VFR intervention for the ankle plantar flexors was reported to be effective in increasing ROM on the nonintervention side to the same extent [ 7 ].…”
Section: Introductionmentioning
confidence: 99%